Establishing the process kinetics and appraising model predictive behavior for coagulation treatment of tannery industry wastewater. Issue 5 (4th May 2022) - Magesh Kumar, M.; Sakthi Saravanan, A.
Abstract: The residual coloring agents present in tannery wastewater degrades the quality of ecosystem and limits photosynthetic activity in aquatic biosphere apart from causing displeasing appearance. This study is conducted to test the ability of protein coagulant extracted from Moringa oleifera (MO) seeds for removing the color from tannery wastewater. Different salt solutions such as NaCl, KCl, MgCl2 and NH4 Cl were used individually to extract the coagulant from MO seeds. The color removal efficiency was the highest for NaCl extracted coagulant (75.14%) and least for MgCl2 extracted coagulant (62.38%). The coagulant extracted for 30 min duration and stored for one day at 278 K removed 75.14% coloring agents from wastewater. The efficiency of NaCl-extracted coagulant was investigated by varying the parameters such as NaCl concentration (0.1 N–0.4 N), initial pH (3–10), coagulant dose (10 mL–50 mL) and coagulant storage temperature (278 K–298K). The differential method of analyzing kinetic data indicates that process obeys second order mechanism because a plot between the rate of change in color intensity and square of the fraction of residual color is a parabolic curve. The interrelationship between response and process variables was studied using linear, exponential, logarithmic, second order polynomial and power law models. Highest color removal of 75.14% was achieved at optimal conditions of 0.2 N NaCl solution, pH 8, 40 mL dose and 278 K storage temperature. It was ascertained that the power law model (R 2 = 0.906) truly reflected the system behavior, while the linear model (R 2 = 0.797) had poor prediction capability.